Ictiofauna como indicadora da qualidade ambiental na Baía do Gaujará (Belém-PA), estuário amazônico - VIANA, Andréa Pontes (Universidade Federal do Pará, 2014)
The Guajará Bay (Belém-PA Metropolitan Area) belongs to the Amazonian estuary and is the geographic accident that most undergoes urban influence. Thus, this work aimed to carry out a study on the health conditions of the estuarine zone of the Bay of the Guajará, by studying the impact of effluent direct release on the water quality using icthyofauna as ecological indicator. Five stations, located in the main channel (4) and igarapés (very narrow arm of the river) (1) were considered contaminated and three references, 2 in main channel and 1 in the igarapé, were selected. Stations have been sampled 4 times along a year. A total of 567 individuals of 40 species have been captured, and the main taxa reported was Siluriforms. The relative abundance in number of individuals (CPUEn) at the main channel showed greater values in December (S/C). Significant catch variation was observed between stations of the Igarapé. The majority of species in igarapés as well as the main channel was considered as occasional. This visiting fauna uses the area for reproduction, nursery and feeding. This choice is due to the food and shelter availability. In terms of diversity, the main channel showed similar results between the periods and stations. The igarapés presented a significant difference between stations only. The multivariate analysis show a clear difference between the icthyofauna inhabiting the main channel and the one caught in igarapés. The species captured in the channel presented, to a large extent, migratory habits, moving between limnological-estuarine and estuarine-coastal environments. Conversely, in igarapés, most species were freshwater species, with individuals carrying out only restricted migrations within the igarapé. Considering the main channel, December (transition dry-rain season) catch was significantly different from others sampled periods. Igarapés catches varied significantly between seasons. The BIO-ENV analysis could not identify environmental factors that would be influencing community structure. We could not identify a direct impact on the fish community by pollutant release from the city of Belém. A biostimulation phenomenon is reported, and may be an initial warning for the potential organic pollution leading to the environment, eutrophisation. This may cause irreparable damages for the environmental and the population that utilizes this place as a resource.